Extreme Alteration of Chevkinite-(Ce) by Pb-CO2-Rich Fluids: Evidence from the White Tundra Pegmatite, Keivy Massif, Kola Peninsula - Ray Macdonald; Bogusław Bagiński; Marcin Stachowicz; Dmitry Zozulya; Jakub Kotowski; Petras Jokubauskas (Minerals, 2022)
An unusual hydrothermal alteration scheme was presented for chevkinite-(Ce) from the White Tundra pegmatite (2656 ± 5 Ma), Keivy massif, Kola Peninsula. Pb-CO2-rich fluids initially removed REE and Y from the chevkinite-(Ce), with enrichment in Pb and U. PbO abundances reaching 17.35 wt%. Continued alteration resulted in the altered chevkinite-(Ce) being progressively transformed to a Pb-Ti-Fe-Si phase, which proved, upon EBSD analysis, to be almost totally amorphous. Pb enrichment was accompanied by a loss of LREE, especially La, relative to HREE, and the development of strong positive Ce anomalies. A notably U-rich aeschynite-(Y), with UO2 values ≤7.67 wt%, crystallized along with the chevkinite-(Ce). Aeschynite-(Y) with a lower UO2 value (3.91 wt%) and bastnäsite-(Ce) formed during alteration. The formation of bastnäsite-(Ce) rather than cerussite, which might have been expected in a high Pb-CO2 environment, is ascribed to the fluids being acidic.